Challenges of SARS-CoV-2 genomic surveillance in India during low positivity rate scenario - Tomar, Siddharth Singh; Khairnar, Krishna (Frontiers in Public Health, 2023)
Being the second most populous country in the world, India presents valuable lessons for the world about dealing with the SARS-CoV-2 pandemic. From this perspective, we attempted a retrospective evaluation of India's SARS-CoV-2 genomic surveillance strategy and also gave some recommendations for undertaking effective genomic surveillance. The dynamics of the COVID-19 pandemic are continuously evolving, and there is a dire need to modulate the genomic surveillance strategy accordingly. The pandemic is now settling towards a low positivity rate scenario, so it is required to revise the practices and policies formulated for a high positivity rate scenario. The perspective also recommends adopting a decentralised approach for SARS-CoV-2 genomic surveillance with a focus on optimising the workflow of SARS-CoV-2 genomic surveillance to ensure early detection of emerging variants, especially in the low positivity rate scenario. The perspective emphasises a key observation that the SARS-CoV-2 genomic surveillance is an important mitigation effort during the pandemic, the guards of such mitigation efforts should not be lowered during the low positivity rate scenario. We attempt to highlight the limitations faced by the Indian healthcare administration during the SARS-CoV-2 genomic surveillance and, simultaneously, suggest solutions derived from our first-hand experience, which may be implementable in a vast, populated country like India.